Possible ways of corporate tax base harmonization in the European Union - Danuše Nerudová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
The possible ways of corporate tax base harmonization in the European Union are presented in the paper. Present situation when there are 27 different taxation systems used in the EU increases compliance costs of taxation to the companies and therefore decreases their competitiveness. It was proved, that there is negative correlation between the size of the company and the size of the compliance costs of taxation. Based on that, the European Commission has decided for twin-track strategy – to introduce home state taxation in the short term and common consolidated corporate tax base in the long term. In respect to the fact, that the pilot project in the frame of home state taxation system has not started yet, the attention has been turned to the common consolidated corporate tax base. The paper discusses the possible attitudes and methods of consolidated tax base allocation. Based on mentioned arguments the formulary apportionment with factors which generate the taxable income of the group (assets, payroll, turnover, etc.) seems to be the best solution. Factors and their weight should become the subject of further discussion in the European Union. The aim of the paper is to present the possible harmonization models and further to discuss the methods which could be used for allocation of the consolidated tax base under CCCTB.